Biodiversity – Handbook of the Anthropocene in Latin America II - Olaf Kaltmeier; Antoine Acker; León Enrique Ávila Romero; Regina Horta Duarte (BiUP, 2024)
Biodiversity should not be understood in biological terms only and as a thing apart from society, but rather as biocultural diversity present in the social world and in various cultures. Such a perspective might allow to relieve social conflicts as well as abuses of power, and slow the appropriation of the biosphere. This volume of the Handbook »The Anthropocene as Multiple Crisis« focuses on biodiversity in the main macro-regions of Latin America from the colonial regime to the contemporary era of the Anthropocene. The contributions enrich contemporary debates surrounding the genealogy of the Anthropocene in Latin America with critical perspectives from the social sciences and the humanities.